Synthesis and cytotoxicity of some acetylated alkaloids of Hymenocallis littoralis - Phuong Anh, Dinh Thi; Duong, Tran Bach; Hoang, Vu Dinh (Vietnam Journal of Chemistry, 2014)
11-O-acetyltazettine (2), 2-O-acetyllycorine (4), 1,2-O,O’-diacetyllycorine (5), and 11-O-acetylhaemanthamine (7) were synthesized  from tazettine (1), lycorine (3) and haemanthamine (6) isolated from the whole plant of Hymenocallis littoralis. Structures of the compounds were elucidated by means of spectroscopic methods. All the alkaloids and their derivatives were tested for cytotoxicity activities to KB and Hep G2 cell lines. Keywords: Hymenocallis littoralis, alkaloid, acetylated derivatives, cytotoxicity activity.